Tumor Characterization with Dynamic Contrast Enhanced Magnetic Resonance Imaging and Biodegradable Macromolecular Contrast Agents in Mice - Wu, Xueming (2009)
PURPOSE: To investigate the efficacy of polydisulfide-based biodegradable macromolecular contrast agents of different degradability and molecular weight for tumor characterization based on angiogenesis using dynamic contrast enhanced MRI (DCE-MRI). METHODS: Biodegradable macromolecular MRI contrast agents, GDCC and GDCP, with molecular weight of 20 and 70 KDa were evaluated for tumor characterization. The DCE-MRI studies were performed in nude mice bearing MDA PCa 2b and PC-3 human prostate tumor xenografts. Tumor angiogenic kinetic parameters, endothelium transfer coefficient (K(trans)) and fractional tumor plasma volume (f(PV)), were calculated from the DCE-MRI data using a two-compartment model. RESULTS: There was no significant difference in the f(PV) values between two tumor models estimated with the same agent except for GDCC-70. The K(trans) values in both tumor models decreased with increasing molecular weight of the agents. GDCC-70 showed a higher K(trans) values than GDCP-70 due to high degradability of the former in both tumor models (p < 0.05). The K(trans) values of MDA PCa 2b tumors were significantly higher than those of PC-3 tumors estimated by Gd(DTPA-BMA), GDCC-20, GDCC-70, GDCP-70, and albumin-(Gd-DTPA) (p < 0.05). CONCLUSIONS: The polydisulfide based biodegradable macromolecular MRI contrast agents are promising in tumor characterization with dynamic contrast enhanced MRI.